Using decision aids to support self-isolation during the COVID-19 pandemic - Pete Lunn; Shane Timmons; Hannah Julienne; Cameron A. Belton; Martina Barjaková; Ciarán Lavin; Féidhlim McGowan (The Economic and Social Research Institute (ESRI), 2020)
Self-isolation is a vital element of efforts to contain COVID-19. We report an online experiment with a nationally representative sample (N=500) that tested behaviourally informed decision aids to support self-isolation. The experiment had three stages that tested interventions designed to help individuals to: (i) decide whether they need to self-isolate; (ii) be confident in their ability to self-isolate should they need to; and (iii) manage a household in which an individual needs to selfisolate. Relative to prevailing public health advice, displaying decision trees improved participants' decisions about when selfisolation was necessary, although they systematically underestimated the need to self-isolate in the presence of less common COVID-19 symptoms (e.g. sore throat, fatigue). Interaction with an online planning tool increased confidence about coping with self-isolation among adults aged under 40. Presenting advice in the form of infographics improved recall and comprehension of how to manage self-isolation. The study demonstrates how public health policy can benefit from behavioural pre-testing of interventions.
Keywords: 330; Selbstorganisation; Soziale Ausgrenzung; Infektionskrankheit; Coronavirus; Coping-Strategie